KEGIATAN PEMERIKSAAN KESEHATAN DAN PENDAFTARAN PESERTA BERBASIS QR CODE PADA MASYARAKAT BENGKONG LAUT BATAM - Farhansyah, Fani; Anisa, Desfa; Natasha (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
People tend not to visit health facilities in good health and prefer to use traditional medicines if they are sick, compared to seeing a doctor. The role of health workers and health educators is urgently needed in increasing public awareness in maintaining health both through socialization and health check-up activities. This health examination was carried out by the lecturers and health students of Awal Bros University, on September 11, 2022. The first activity was carried out by recording or registering the people who were present using QR Code registration after which it was continued with a free health check. This activity is intended for all residents of Bengkong Laut Batam. Participants in this community activity attended and came directly to the location of the activity. The number of participants who took part in this activity were 32 people. The method of community service activities is carried out in the form of discussions and practical methods. This practical method is carried out by examining the health of the participants directly, such as measuring blood pressure and checking blood glucose.